Взаимодействие фаз в системе B–BN при высоких давлениях - Туркевич, В.З.; Соложенко, В.Л.; Туркевич, Д.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Phase interaction in the B–BN system has been studied at high pressure and temperature. Experimental investigations of boron subnitrides B₆N and B₅₀N₂ formation have been carried out. The phase diagram of the B–BN system at 5 GPa was thermodynamically calculated.